2016
DOI: 10.1017/s0022377816000428
|View full text |Cite
|
Sign up to set email alerts
|

Pair production by Schwinger and Breit–Wheeler processes in bi-frequent fields

Abstract: Counter-propagating and suitably polarized light (laser) beams can provide conditions for pair production. Here, we consider in more detail the following two situations: (i) in the homogeneity regions of anti-nodes of linearly polarized ultra-high intensity laser beams, the Schwinger process is dynamically assisted by a second high-frequency field, e.g. by an XFEL beam; and (ii) a high-energy probe photon beam colliding with a superposition of co-propagating intense laser and XFEL beams gives rise to the laser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 49 publications
0
13
1
Order By: Relevance
“…In contrast to the works on the bifrequent mechanism of vacuum EPP excitation [2,3] the present investigation has shown that the transition in the few photon area ensures in itself a high intensity of the EPP creation process without participation of the tunneling mechanism. This is the main result of this work.…”
Section: Resultscontrasting
confidence: 99%
“…In contrast to the works on the bifrequent mechanism of vacuum EPP excitation [2,3] the present investigation has shown that the transition in the few photon area ensures in itself a high intensity of the EPP creation process without participation of the tunneling mechanism. This is the main result of this work.…”
Section: Resultscontrasting
confidence: 99%
“…Various aspects, such as the impact of the pulse envelope, pulse duration, and pulse polarization of e þ e − pair creation in single pulses were analyzed, e.g., in Refs. [20][21][22][23][24] with special emphasis on CEP effects [13,14], spin effects [25], bi-frequent pulses [26][27][28], spectral caustics [27], and focusing effects [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Our paper is organized as follows. Section 2 deals with the laser assisted Breit-Wheeler process, where spectral caustics have been identified already in [17,18]. Specifically, we deliver here as new result the phase space distribution of positrons, in particular the double-differential cross section as a function of longitudinal and transverse momenta.…”
Section: Introductionmentioning
confidence: 97%